ANALISIS KESULITAN MENYELESAIKAN SOAL PEMECAHAN MASALAH MATERI BANGUN RUANG SISI DATAR BERBASIS ETNOMATEMATIKA BENGKULU SELATAN - Ratih Kristantini (Prodi Pendidikan Matematika FKIP Universitas HKBP Nommensen, 2022)
This study aims to describe students’ difficulties in solving the problem of waking up flat side spaces. The type of research used in this study is qualitative descriptive. The instrument used in this study was the observation, tests, and interviews. The results of the study were obtained that: 1) Students are still in difficulty considering the formula and difficulty completing problems according to the procedure so students struggle with the concept and algorithm. 2) Students are still struggling in explaining the formula, determining the final answer, having difficulty in completing the formula for answers, and not being able to determine the high side of the fives in the form of a triangle so students still struggle with the concept, principles, and algorithm. 3) Students have difficulty determining the final answer, unable to understand the calculation of their contemporaries so students have difficulty with the principle and algorithms.